Fish diversity along spatial gradients in the Itaipu Reservoir, Paraná, Brazil - Oliveira,E. F. (2004)
Local and turnover patterns of fish diversity in the Itaipu Reservoir were evaluated and related to a longitudinal or river-dam gradient (composed of riverine, transitional, and lacustrine zones) and to transversal or upstream-downstream gradients of the tributaries (composed of lotic and lentic stretches of tributaries and reservoir shores). Thirteen stations were sampled quarterly during 2 years. A total of 85 fish species were caught. Local (alpha) and turnover (beta) patterns of fish diversity showed significant differences in reservoir spatial gradients. Along the longitudinal gradient, total and alpha-diversity were the highest in the riverine and transitional zones of the reservoir and lowest in the lacustrine zone. Along the transversal gradient, total and alpha-diversity increased from the lotic stretches of the tributaries to the reservoir shores. The lotic and lentic stretches of the tributaries presented the highest beta-diversity values, indicating heterogeneity in species compositions among the sub-basins. We conclude with recommendations for reservoir management based on the results of this study.